Business Processes of Indian Vaccine Manufacturers - Bhargava, Nyayapati Sunil Narayana (Global journal of Business and Integral Security, 2024)
The vaccine industry, or vaccine manufacturing, is a highly sophisticated and niche area in the field of biopharmaceuticals or biotechnology, which forms part of the pharmaceutical industry. Biopharma is defined as "any pharmaceutical product derived from biological sources, especially one produced by biotechnology.‖ The vaccine segment is one of the most important parts of the Biopharma offering, with a high emphasis on the preventive management of diseases. Unlike the pharmaceutical industry, the vaccine industry is highly regulated, highly capital-intensive, and requires sophisticated manufacturing facilities to manage biological materials and standardize output as per regulatory norms. Strength in advanced research and research platforms in the field of vaccines and biotechnology gives the manufacturer an edge in the industry. India is one of the highest-quality and lowest-cost manufacturers of vaccines in the world, accounting for more than 60% of the world‘s requirements. Although vaccine manufacturing facilities require equipment to manage viruses, bacteria, and other microorganisms, the industry has specialized fields in human and animal (veterinary) vaccines. Indian vaccine manufacturers have grown over time to do active research, introduce newer vaccines, and design manufacturing facilities based on technology. Such new vaccines give an advantage to the manufacturers as first movers to gain premium in the retail market, and later, when the product finds more manufacturers or is adopted by state-run programs, the premium advantage of the vaccine ceases to exist. Vaccines manufactured in India are low-cost in nature, and UNICEF usually ropes in these manufacturers for worldwide supplies to reduce the cost of procurement of vaccines. The Indian vaccine industry has always been a subset of the pharmaceutical industry, and hence, business processes and other methods of evaluation of the vaccine industry in India have always followed the pharmaceutical business template. Hence, this research aimed to examine the vaccine industry and its business processes. Further, this research is to explore the attributes that are related to the pharmaceutical and vaccine business processes. This is an exploratory and explanatory study to accomplish the research objectives by exploring insights in the Indian vaccine industry. Research studies include publications (research studies, paper publications, news, and articles), magazines, questionnaires (Google Forms) for important personnel in the industry, personal discussions, data from profit and loss statements, balance sheets of companies, progress of select companies through historical data, progress of technology, business model evaluation, existing literature, and both qualitative and quantitative evaluation of the Indian vaccine industry. Out of the total estimated 32 vaccine manufacturing companies, about nine are state-run companies, and hence 25% of the samples were drawn from the remaining twenty-three companies. Seven companies responded, which include two multinational companies and one PSU, in line with the research design and proposal. Collected data, key information, and patterns were analysed. Research produced key findings through various questionnaires and analyses related to the objectives. 1. The inherent factors that influence the vaccine business and business models are unlike the pharma business model. 2. practices in the industry to sustain business models and identify the customer selection compulsions of the manufacturer. 3. Classification of the vaccine industry is also vital, given the diversified nature of variables and 4. Parameters set by rating agencies such as CRISIL for each company based on their in- house metrics However, due to inherent risks and long lead times in delivering vaccines, rating agencies should find additional parameters to set ratings and suggest ratings for the vaccine industry other than the conventional ones. The key inferences or conclusions drawn from this research imply the stark differences between the vaccine industry operated in India and the selection of customers, which cannot be compared with pharmaceutical industry models. Consequently, the research findings and recommendations will help further refine the new classifications, rating systems, and evaluation systems for the vaccine industry in India.